2-Hydroxy-(2-methyl-1H-indol-3-yl-methylidene)benzohydrazide ethanol solvate - Ariffin, Azhar; Ng, S.W.; Yehye, W.A. (International Union of Crystallography, 2008)
In the title compound, C17H15N3O2 center dot C2H6O, Schiff base molecules are linked by a hydroxy-amido hydrogen bond into a helical chain running along the b axis. This chain is consolidated by two other hydrogen bonds; the ethanol solvent molecule is a hydrogen-bond donor to the amide group and a hydrogen-bond acceptor for the indolyl NH group of an adjacent Schiff base molecule.